Diagnostic setup for the divertor manipulator at wendelstein 7-X. (January 2019) - Hubeny, M.; Höschen, D.; Rack, M.; Neubauer, O.; Bozhenkov, S.; Czymek, G.; Unterberg, B.; König, R.; Hathiramani, D.; Brezinsek, S.; Linsmeier, Ch.
Highlights: W7-X discharges allows reactor-relevant exposure of plasma facing components. Versatile divertor manipulator system enables investigating and resolving many PWI processes by extended diagnostic coverage. Laser injection and observation system needed to harness full potential of divertor manipulator. Abstract: The investigation of plasma wall interactions in terms of erosion processes, fuel retention and new plasma facing components exhibits a scientific gap as discharges in tokamaks and stellarators last only seconds up to a minute. Currently, linear plasma machines are bridging this gap, while Wendelstein 7-X (W7-X) will provide steady-state discharges of up to 30 min in its second operation phase (OP2), in which a divertor manipulator is envisaged to expose samples to reactor-relevant plasma fluxes and fluences. With a design following the limiter lock system at TEXTOR and the DIM-II at ASDEX Upgrade (AUG), the divertor manipulator at W7-X aims to study plasma surface interactions ex-situ by daily/weekly probe exchange and in-situ by embedded diagnostics and an observation system. The design, layout and capabilities of the embedded and observing diagnostics determine the accessible parameters for the in-situ investigation of the exposed probe materials, ranging from plasma edge measurements in the manipulator shaft to intersecting the magnetic island structure on the manipulator head. A versatile laser and observation system adds active surface analysis techniques. To prevent local overheating and excess thermal stress, essential diagnostics for temperature control are identified and combined with first considerations of the manipulator head shaping, based on the field line tracing tool of the W7-X web-service.